Directing professionally : a practical guide to developing a successful career in today's theatre - Thompson, Kent (Artistic Director) (Introductions to theatre, 2019)
"How do you develop both the craft of directing as well as a professional career in freelance directing in today's theatre industry? Drawing on his own extensive experience and that of other theatre professionals from the US and UK, Kent Thompson illuminates a pathway from training, apprenticeship and assistant directing to an established career as a director. Directing Professionally first lays out paths for aspirant directors to train, grow and succeed as directors, then advises freelance directors on how to establish and accelerate their professional careers. It also reveals the most significant ways those directors become artistic directors today. With a frank, thoughtful and often humorous examination of the job of professional direction and artistic direction, Thompson writes about the passion, commitment, artistic vision, directorial experience, leadership skills, and powerful persuasive gifts needed to succeed in this extraordinary field. Featuring case studies and brief interviews with professional theatre directors, artistic directors, producers, critics, managing/executive directors, and theatre leaders currently working in the field in the UK and the US, this volume will equip you to develop your career as a professional director in today's theatre"--